2009
DOI: 10.4038/rjs.v4i0.57
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and comparison of salt content in mangrove plants in Sri Lanka

Abstract: Due to the predicted threats of global warming and sea level rise, the salt tolerance and salt accumulative abilities of plants have become popular contentious topics. Mangroves are one of the major groups of salt tolerant plants and several mechanisms are known as instrumental in their salt tolerance. Salt excretion through leaf drop is given as one, but its validity is questioned by some recent works compelling the necessity for further studies. Knowledge of the salt contents in different mangrove plants is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Exceeding critical cytoplasmic Na + and Cl + concentrations can cause damage in halophytes, resulting in a reduction of the net photosynthesis rate through stomatal closure (Himabindu et al, 2016). Mangrove leaves, for example, accumulate salt as they mature (Cram et al, 2002) to levels up to 12 times higher compared to freshwater plants (Dissanayake & Amarasena, 2009). Furthermore, experiments have shown that the salt content in the leaves of red mangroves growing in high‐salt environments is significantly higher than the leaf salt content of plants in low‐salt environments (Lin & Sternberg, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Exceeding critical cytoplasmic Na + and Cl + concentrations can cause damage in halophytes, resulting in a reduction of the net photosynthesis rate through stomatal closure (Himabindu et al, 2016). Mangrove leaves, for example, accumulate salt as they mature (Cram et al, 2002) to levels up to 12 times higher compared to freshwater plants (Dissanayake & Amarasena, 2009). Furthermore, experiments have shown that the salt content in the leaves of red mangroves growing in high‐salt environments is significantly higher than the leaf salt content of plants in low‐salt environments (Lin & Sternberg, 1992).…”
Section: Discussionmentioning
confidence: 99%